Controversies in Psychotherapy and Counselling. - Feltham, Colin (Sage Publications, 1999)
|My congratulations to Colin Feltham for assembling a set of contentious issues and lively authors which together made me forget my surroundings' - Person-Centred Practice. |Editor Colin Feltham's choice of topics shows an astute, on-the-ground awareness of the issues that dog the industry, while still making lively reading' - New Therapist. In this book, leading practitioners, critics and commentators take sides on many topical and core debates including: * Theoretical issues: Does the unconscious really exist? Is birth trauma a fiction? Should one believe in |false memories'? * Clinical issu.